Quo vadis plant hormone analysis? - Tarkowská, Danuše; Novák, Ondřej; Floková, Kristýna; Tarkowski, Petr; Turečková, Veronika; Grúz, Jiří; Rolčík, Jakub; Strnad, Miroslav (Planta, 2014)
Plant hormones act as chemical messengers in the regulation of myriads of physiological processes that occur in plants. To date, nine groups of plant hormones have been identified and more will probably be discovered. Furthermore, members of each group may participate in the regulation of physiological responses in planta both alone and in concert with members of either the same group or other groups. The ideal way to study biochemical processes involving these signalling molecules is 'hormone profiling', i.e. quantification of not only the hormones themselves, but also their biosynthetic precursors and metabolites in plant tissues. However, this is highly challenging since trace amounts of all of these substances are present in highly complex plant matrices. Here, we review advances, current trends and future perspectives in the analysis of all currently known plant hormones and the associated problems of extracting them from plant tissues and separating them from the numerous potentially interfering compounds.
Keywords: rostliny; Plants; regulátory růstu rostlin; signální transdukce; Plant Growth Regulators; Signal Transduction